PENGARUH STAKEHOLDER PRESSURE DAN OWNERSHIP STRUCTURE TERHADAP KUALITAS SUSTAINABILITY REPORT - Ananda Firdzah Zatalini, (2022)
This study aims to analyze and develop a conceptual framework that examines the influence of Stakeholder pressure and Corporate Governance and its effect on Sustainability Report Quality. This research was conducted quantitatively with secondary data from sustainability reports and annual reports of the companies listed on IDX for the 2018-2020 period with a research sample of 35 companies from all sectors. The hypothesis testing of this study is using Multiple Linear Regression Analysis with the help of the STATA 14.2 program. The test results show that on sustainability report quality; (1) environmentally sensitive industries have a positive and significant effect, (2) customer-proximity industries have a positive and significant impact, (3) employee-oriented industries have no significant effect, (4) investor-oriented industries have no significant effect, (5) family ownership has no significant effect, (6) managerial ownership has no significant effect, (7) foreign ownership has no significant effect, (8) profitability as a control variable has a negative and significant effect, while firm size and Leverage has no significant effect.